PENGARUH APLIKASI BAHAN ORGANIK PEMBENAH TANAH TERHADAP SIFAT KIMIA TANAH, PERTUMBUHAN DAN PRODUKSI TANAMAN TEBU DI KEBUN PERCOBAAN PABRIK GULA BONE, KABUPATEN BONE - Kisman Topani; Bambang Siswanto; Retno Suntari (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Coal is one of the fossil fuel non-oil that can be burned, from sedimentary, organic rock composed mainly of carbon, hydrogen and oxygen. However, the use of coal still produces waste that remains to be addressed, such as fly ash. In the sugar industry, also contained fly ash (boiler ash or Bagasse ash) generated using bagasse (bagasse) as fuel. The research objective: 1) know the capabilities of soil amendment application to the chemical soil properties; 2) Determine the effect of soil amendment application on sugarcane plant growth; 3) know the efficiency of soil amendment application on the production. This experiment used a randomized block design (RBD) with six treatments of P1 (Control), P2 (Control + Compost), P3 (Control + Compost + Boiler Ash), P4 (Control + Boiler Ash), P5 (Control + Boiler Ash without Potassium fertilizer), and P6 (Control + Boiler Ash without Dolomite application) with three replications. Then, the data were analyzed by analysis of variance followed by Duncan test 5%. The results of study showed that the treatment of soil amendment organic matter application with a combination treatment of inorganic fertilizers + compost 6 t ha-1 + boiler ash 40 t ha-1 (P3), was able to repair and improve the content of N, P, K, pH, organic C and soil CEC. The treatment of soil amendment organic matter application with a combination of inorganic fertilizer + compost 6 t ha-1 + boiler ash 40 t ha-1 (P3), was able to improve and enhance the growth of sugar cane plant height, number of tillers, and the diameter of the cane. The treatment of soil amendment organic matter application with a combination of inorganic fertilizer + compost 6 t ha-1 + boiler ash 40 t ha-1 (P3), was able to increase the yield of crop production and had the highest value